1997
DOI: 10.1142/s0218625x97000079
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY ABSORPTION SPECTROSCOPY STUDY OF THIN ZnO FILMS GROWN BY SINGLE SOURCE CVD ON Si(100)

Abstract: In situ X-ray absorption spectroscopy analysis of early states of ZnO film growth on Si(100) by single source chemical vapor deposition (CVD) has been performed using basic zinc acetate as precursor. A high concentration of carbon is detected at the interface, which decreases with increasing film thickness (~2 nm thickness), and as expected there is some oxidization of the Si surface. This is explained by the chemical nature of the immediate surface upon which the deposition takes place, varying from a reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…(1) Onset of Self-Texture. Recently, the utilization of angle dependent NEXAFS measurements as a “fingerprint” of the symmetry type in films has been demonstrated. , In Figure the O 1s NEXAFS measurements for a ∼500 nm thick, polycrystalline and c -axis oriented ZnO reference film are shown for two different angles, ϑ, between the electric field vector of the synchrotron radiation and the surface plane. For this orientation, the ZnO unit cells are arranged with the c -axis perpendicular to the substrate surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Onset of Self-Texture. Recently, the utilization of angle dependent NEXAFS measurements as a “fingerprint” of the symmetry type in films has been demonstrated. , In Figure the O 1s NEXAFS measurements for a ∼500 nm thick, polycrystalline and c -axis oriented ZnO reference film are shown for two different angles, ϑ, between the electric field vector of the synchrotron radiation and the surface plane. For this orientation, the ZnO unit cells are arranged with the c -axis perpendicular to the substrate surface.…”
Section: Resultsmentioning
confidence: 99%
“…The main features can be assigned to CCπ* (at ∼285 eV), CHπ*/COπ* (at ∼288 eV), and CCs* (at ∼293 eV) resonances . For comparison a C 1s NEXAFS spectrum obtained from a ZnO film deposited with no water ambient (thickness 20 Å) is shown in the inset in Figure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…conc.) compared to carbon free sputtered films, this carbon being situated in the buffer layer and the grain boundaries of the crystallites 16,17 . TEM analysis of these same films indicated that while the crystallites were c-axis oriented, there was no preferred orientation of the a,b-axes within each column i.e.…”
Section: Atomic Force Microscopy Measurements (Local Piezoelectric Efmentioning
confidence: 99%
“…This technique has been described previously. [13] In our SSCVD depositions of ZnO, we have used zinc carboxylates, [13,14] zinc β-diketonates and zinc oximates [15] as precursors. However, ideal single-source behaviour was only observed with the (carbamato)zinc complex [Zn 44 -O)(O 2 CNEt 2 ) 6 ], [12] as the other precursors required additional oxygen sources to suppress the formation of high-carbon amorphous ZnO.…”
Section: Introductionmentioning
confidence: 99%